Prevalence and Coping Strategies of Postnatal Depression among Women in Bayelsa State, Nigeria - Uzobo, Endurance; Teibowei, Bodisere Juliet; Ogeh, Victoria Imomoemi (Africa Journal of Nursing and Midwifery, 2022)
This study examined the prevalence and coping strategies of Postnatal Depression (PND) among mothers in Bayelsa, the state of Nigeria. The general aim was to describe the level of PND experienced by women and the methods they adopt to cope with this syndrome. This study was a cross-sectional survey of 345 women with babies between 1-6 weeks old. The women were selected purposively at health and maternity centres and clinics in Bayelsa state. A structured questionnaire was used in data collection. The data gathered were analysed using univariate, bivariate and multivariate analyses at a p≤0.05 level of significance. The prevalence rate of PND ranged from mild depression (37.7%), moderate depression (3.5%) to severe depression (3.2%). There is a statistically significant relationship between socio-demographic variables and PND among mothers (p=0.000). PND prevalent among the study population exerts adverse effects on the health and cognitive development of the mother and child. However, the strategies adopted by mothers to cope with PND ranged from social support to music therapy. This study recommended that counselling of mothers during and after childbirth should be carried out as part of the routine for mothers and childcare.